Agricultural growth trends and outlook report: Trends in agricultural sector performance, growth and poverty in Malawi - Matchaya, Greenwell C.; Phiri, Alexander; Chilonda, Pius; Musaba, Emmanuel (International Water Management Institute, 2014)
This report presents results of the 2012 Annual Trends and Outlook for Malawi (ATOR). This is the first ATOR for Malawi. The study was carried out as part of the Southern African Development Community (SADC) Monitoring and Evaluation for the Comprehensive Africa Agriculture Development Program (CAADP) Survey. The study mainly adopted a quantitative approach. A standard structured questionnaire 1 was used to collect data on several indicators around the six broad areas. They are: i) the CAADP implementation process; ii) public spending and investment indicators; iii) output indicators (agricultural technology, diffusion and human capital indicators; iv) agricultural sector performance indicators (agricultural production and trade indicators; v) macro and socioeconomic indicators (welfare indicators); and vi) agricultural development strategies, policies and/or plans. The time series data covered the period from 2000 to 2011, but in some cases information for 2012 was also collected. The analysis of the data involved calculation of percentages, means, drawing of graphs and synthesis of the information to determine the trends in the main indicators from the dataset. A standard template for the structure of the report was provided by ReSAKSS-SA coordination office.